Survivors of infant atypical teratoid/rhabdoid tumors present with severely impaired cognitive functions especially for fluid intelligence and visual processing: data from the German brain tumor studies - Traunwieser, Thomas; Loos, Elena; Ottensmeier, Holger; Gastberger, Katharina; Nemes, Karolina; Mynarek, Martin; Bison, Brigitte; Kandels, Daniela; Neumayer, Petra; Neumann-Holbeck, Anne; Lüttich, Peggy; Baust, Katja; et al. (Pediatric blood & cancer, 2024)
Background The contribution of tumor type, multimodal treatment, and other patient-related factors upon long-term cognitive sequelae in infant brain tumor survivors remains undefined. We add our retrospective analysis of neuropsychological and quality of survival (QoS) outcome data of survivors of atypical teratoid/rhabdoid tumors (ATRT) and extracranial malignant rhabdoid tumors of the soft tissues (eMRT) and kidneys (RTK) treated within the same framework. Neuropsychological data from children with ATRT were compared to data from children with non-irradiated low-grade glioma (LGG). Patients and methods Following surgery, patients (0-36 months at diagnosis) had received radio-chemotherapy (up to 54 Gy; ATRT: n = 13; eMRT/RTK: n = 7), chemotherapy only (LGG: n = 4; eMRT/RTK: n = 1) or had been observed (LGG: n = 11). Neuropsychological evaluation employing comparable tests was performed at median 6.8 years (ATRT), 6.6 years (eMRT/RTK), and 5.2 years (LGG) post diagnosis. Results We detected sequelae in various domains for all tumor types. Group comparison showed impairments, specifically in fluid intelligence (p = .041; d = 1.11) and visual processing (p = .001; d = 2.09) in ATRT patients when compared to LGG patients. Results for psychomotor speed and attention abilities were significantly below the norm for both groups (p < .001-.019; d = 0.79-1.90). Diagnosis predicted impairments of cognitive outcome, while sex- and age-related variables did not. QoS outcome for all rhabdoid patients displayed impairments mainly in social (p = .008; d = 0.74) and school functioning (p = .048; d = 0.67), as well as lower overall scores in psychosocial functioning (p = .023; d = 0.78) and quality of life (p = .006; d = 0.79) compared to healthy controls. Conclusion Survivors of infant ATRT experience various late effects in cognition and QoS following multimodal treatment, while infant LGG patients without radiotherapy demonstrated comparable impairments in psychomotor and attention abilities. Early onset and multimodal treatment of rhabdoid tumors require close monitoring of neuropsychological and QoS sequelae.